ANALISIS FINANSIAL DAN TATA NIAGA PENGUSAHAAN JAMUR TIRAM PUTIH (Pleurotus sp) DI KABUPATEN OKU TIMUR (JASEP, 2019)
Oyter mushroom cultivation has good economic prospects. The oyster mushroom market that has been clear and market demand is always high makes it easy for farmer to market the produktion of oyster mushrooms. Oyster mushroomis one of the comercial products and can be developed with a simple technique. Raw materials needed are cheap and easily obtained materials such as sawdust, bran and lime, while the cultivation process does not require various pestisides or other chemicals. Beside, the market potential of oyster mushroom is still very open and has economic value. Because it can be consumed by all people. Based on the aspect of biology, oyster mushroom are relatively easier to cultivate and do not require extensive land. The producion period of oyster mushrooms is relatively faster so that the harvest period and time are shorter and can be continous. Oyster mushroom cultivation can be managed as a side business or small, medium, and large (industrial) economic business. The objectives of this study were : 1. To analyze the feasibility of farming white oyster mushrooms in the East OKU financially to be developed. 2. Analyze the oyster mushroom trading system in East OKU. 3. Analyze whether the marketing agent of the collecting trader is more efficient than the retailer marketing agency. The result show that financially the cultivation of white oyster mushroom in East OKU is feasible because it has an economic value of R/C ratio 1,3 and a payback period of 17, 22 ( 3,4 periods ). The efficiency of the white oyster mushroom marketing channel includes the highest marketing margin located at retailers, namely Rp 2.250-, /kg compared to collectors who only Rp 2.050-, /kg because the prices offered by retailers are higher than collectors and farmers share is 79,1 %. Traders are more efficient at 4,25 % compared to retaillers of 4,57 %. This is due to the selling price and marketing costs incured by the retailler is greater than the collecting trader.